Immunotherapy in Pediatric Solid Tumors - Jung Yoon Choi (The Korean Society of Pediatric Hematology-Oncology, 2020)
The survival rates for pediatric patients with solid tumors have improved dramatically in recent decades. However, patients with metastatic disease at diagnosis or progressive solid tumors still have a poor prognosis. Recently, immunotherapy has emerged as a novel therapeutic strategy in the pediatric population. Although not widely used in Korea, the anti-GD2 treatment in neuroblastoma is one of the successes of immunotherapy. In addition, many early phase clinical trials for monoclonal and bispecific antibodies, immune checkpoint inhibitors (ICIs), chimeric antigen receptor T cell therapy and cancer vaccines are ongoing. According to results reported so far, a majority of pediatric solid tumors showed limited response to ICIs, except Hodgkin lymphoma and hypermutant pediatric tumors. These results indicate that children and adolescents need to be applied different immunotherapeutic approaches from adults. The aim of this review is to understand the immunological environment and immunotherapeutic challenges in pediatric solid tumors.